2014
DOI: 10.1063/1.4892895
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and rovibrational properties of ZnOH in the $\tilde{X}\; ^{2}A^\prime$X̃2A′ electronic state: A computational molecular spectroscopy study

Abstract: The three-dimensional ground-state potential energy surface of ZnOH has been calculated ab initio at the MR-SDCI+Q_DK3/[QZP ANO-RCC (Zn, O, H)] level of theory and used as basis for a study of the rovibrational properties carried out by means of the program MORBID (Morse Oscillator Rigid Bender Internal Dynamics). The electronic ground state is  (2)A' (correlating with (2)Σ(+) at the linear configuration). The equilibrium structure has r(e)(Zn-O) = 1.8028 Å, r(e)(O-H) = 0.9606 Å, and ∠e(Zn-O-H) = 114.9°. The Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…We followed the procedure outlined in the previous section, and found that the molecule is indeed bent in its ground electronic state ( 2 A state), unlike in the case of YbOH [30]. Although one may expect a metal-hydroxide molecule to be linear on grounds of the ionic nature of its bonding, a bent structure for HgOH indicates that the bond may possess a hint of covalent nature too, similar to the case of ZnOH [48,49]. We determined the optimized R Hg−O to be 2.2294 Å and R O−H to be 0.9633 Å, with the HgOH bond angle (θ Hg−O−H ) being 104.83 • .…”
Section: Resultsmentioning
confidence: 97%
“…We followed the procedure outlined in the previous section, and found that the molecule is indeed bent in its ground electronic state ( 2 A state), unlike in the case of YbOH [30]. Although one may expect a metal-hydroxide molecule to be linear on grounds of the ionic nature of its bonding, a bent structure for HgOH indicates that the bond may possess a hint of covalent nature too, similar to the case of ZnOH [48,49]. We determined the optimized R Hg−O to be 2.2294 Å and R O−H to be 0.9633 Å, with the HgOH bond angle (θ Hg−O−H ) being 104.83 • .…”
Section: Resultsmentioning
confidence: 97%
“…For the other cases including quasi-linear (c 0 % 0) and bent (c 0 % 1) molecules, the c 0 -values reported in our previous studies are compiled in Ref. [56] as Table X therein. If the fundamental and overtone bending transitions of a molecule have been observed experimentally and analyzed, the Yamada-Winnewisser quasi-linearity parameter can easily be derived from the observed vibrational energy spacings.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…To shed new light on this long-standing problem, we have proposed to calculate ro-vibrationally averaged bond lengths and angle as expectation values over the relevant ro-vibrational wavefunctions. We have applied this method to several three-atom molecules [26,27,29,31,33,[54][55][56] and were able to obtain reasonable ro-vibrationally averaged structures. We found that in many cases, the experimentally derived bond lengths for the lighter atom pair (C-N, N-C, or O-H) in the molecule are too short in comparison with the calculated expectation values.…”
Section: Ro-vibrationally Averaged Structuresmentioning
confidence: 96%
See 2 more Smart Citations